The relationship between functional capacity, muscle size and strength in chronic ACL deficient and ACL reconstructed individuals - A. St Clair Gibson; M. I. Lambert; K. H. Myburgh; J. Walters; C. L. Vaughan; M. J. O'Malley; T. D. Noakes (AOSIS, 2000)
Aim: The aim of this study was to assess the relationship between the quadriceps muscle atrophy and strength deficits caused by chronic ACL deficiency, and to ascertain whether these deficits were rectified in subjects who had undergone ACL reconstruction. Methods: Thirteen ACL deficient subjects (ACLD) and eight subjects who had undergone ACL reconstruction (ACLR) participated in the study. Functional capacity, lean thigh volume (LTV), and isokinetic peak torque of the quadriceps and hamstrings muscles were assessed. Results: The ACLD group had a significantly lower score for episodes of giving way compared to the ACLR group (7.4 +/- 3.8 vs. 18.0 +/- 3.7; p < 0.01) and a lower score for inability to perform jumping/twisting activities (1.8 +/- 0.8 vs. 3.6 +/- 1.1; p <0.01; ACLD vs. ACLR) suggesting decreased functional capacity. However, there was no significant difference between the ACLD group and ACLR group for LTV differences (416.0 +/- 276.5 vs. 238.3 +/- 224.4 cc) and quadriceps eccentric peak torque differences (38.1 +/- 13.7 vs. 23.7 +/- 18.3 Nm) between involved and uninvolved limbs. The relationship between LTV and quadriceps isokinetic peak torque was r = 0.59 (p < 0.05) for the ACLD group and r = 0.50 (NS) for the ACLR group. Conclusion: Quadriceps strength deficits are present in ACL deficient subjects, particularly during eccentric contractions. ACL reconstruction improved subjective function and reduced the episodes of giving way, but did not prevent eccentric quadriceps muscle weakness. A low correlation exists between reported function and LTV and eccentric peak torque activity, and between LTV and eccentric peak torque in both ACLD and ACLR groups. These findings suggest that factors other than muscle atrophy are responsible for the functional changes described, in ACL deficient and. ACL reconstructed groups.